2014
DOI: 10.1371/journal.pone.0111250
|View full text |Cite
|
Sign up to set email alerts
|

Surface Microbiology of the iPad Tablet Computer and the Potential to Serve as a Fomite in Both Inpatient Practice Settings as Well as Outside of the Hospital Environment

Abstract: BackgroundThe use of tablet computers and other touch screen technology within the healthcare system has rapidly expanded. It has been reported that these devices can harbor pathogens in hospitals; however, much less is known about what pathogens they can harbor when used outside the hospital environment compared to hospital practice.MethodsThirty iPads belonging to faculty with a variety of practice settings were sampled to determine the presence and quantity of clinically-relevant organisms. Flocked nylon sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Of these, 174 were selected for full-text review, of which 99 did not meet our criteria and were excluded, leaving a total of 75 studies in the final analysis (figure 1). 16–90…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 174 were selected for full-text review, of which 99 did not meet our criteria and were excluded, leaving a total of 75 studies in the final analysis (figure 1). 16–90…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (50) reported primarily on device contamination rates (mostly using cross-sectional samples) 17–23 26 29 32–36 38 41–46 49 50 52–56 60 62 64–66 68–76 81–86 90. Another 25 studies used interventional designs16 24 25 27 28 30 31 37 39 40 47 48 57–59 61 63 67 77–80 87–89; most reported contamination rates before and after a disinfection or cleaning process (and therefore also contributed data on baseline contamination rates).…”
Section: Resultsmentioning
confidence: 99%
“…35 The increasing use of personal electronic devices such as tablet computers in healthcare has introduced a new source of contamination and risk of transmission. 36 Outside the operating room, recommendations for professional dress vary with institutional policies and provider expectations (eg, white coats, scrubs vs dress clothes). Although there is no standard requirement for laundering professional wear, all clothing can be contaminated and has the potential to transmit disease when bacterial cross-contamination between patients occurs.…”
Section: Preventive Strategiesmentioning
confidence: 99%
“…Keyboards can be as easily disinfected with or without covers using five seconds of friction and a wide range of low‐level disinfectant solutions The possibility of microorganism contamination of portable electronic devices (for example, mobile phones, tablets and so on) used in the practice should be considered by optometrists, when using such devices . Hands should be washed before using these devices after touching the patient or eating food and so on.…”
Section: Daily Consulting Room Hygienementioning
confidence: 99%